Antibacterial Activity and TLC-Densitometric Analysis of Secondary Metabolites in the Leaves of the Traditional Herb, Melastoma malabathricum L. - Dian Mayasari; Yosi Bayu Murti; Sylvia Utami Tunjung Pratiwi; Sudarsono Sudarsono (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Indonesia is rich in the biodiversity of medicinal plants used traditionally for healing several ailments. Melastoma malabathricum L. is one of the traditional herbs used to treat many diseases. A TLC-densitometric method was developed for determining secondary metabolites such as phenolic compounds and their related compounds, M. malabathricum leaves from Riau, Indonesia. This study investigated the secondary metabolites of M. malabathricum extract by spraying reagent: FeCl3, p-anisaldehyde, and cerium (IV) sulfate and followed by antibacterial assay through broth macro dilution method. Densitometric qualitative analysis of phenolic compounds and their related compounds was employed to examine peaks of the M. malabathricum extract through winCATS software. After spraying with particular reagents, the three extracts showed various spots/bands with several colors and exhibited peaks in TLC densitogram profiles. Three extracts were tested for antibacterial activity against Staphylococcus aureus and Escherichia coli. The result showed that ethyl acetate extract revealed excellent antibacterial activity against S. aureus and E. coli with MIC values of 3.125±0.6 mg/mL and 6.25±0.5 mg/mL, respectively. Owing to the presence of a wide variety of secondary metabolites, the leaf extract of M. malabathricum is expected to exhibit and help develop as a therapeutic agent.